Iron(III)-substituted polyoxotungstates immobilized on silica nanoparticles: novel oxidative heterogeneous catalysts - Sousa, JLC
Silica nanoparticles supporting polyoxometalates (POMs), namely an iron(III) mono-substituted Keggin-type polyoxotungstate of formula alpha-[PW(11)Fe(III)(H(2)O)O(39)](4-) and a sandwich-type tungstophosphate with the formula B-alpha-[(PW(9)O(34))(2)Fe(4)(III)(H(2)O)(2)](6-) were synthesized. The POM/SiO(2) nanocomposites were obtained by alkaline hydrolysis of tetraethoxysilane using a reverse micelle and sol-gel technique. The spectroscopic studies suggest that the POMs were successfully immobilized on the silica nanoparticles. The catalytic activity of POM/SiO(2) nanomaterials was tested in the epoxidation of geraniol using H(2)O(2) as oxygen donor. The alpha-[PW(11)Fe(III)(H(2)O)O(39)](4-)/SiO(2) nanocomposite was the most efficient catalyst with high geraniol conversion and good regioselectivity for 2,3-epoxygeraniol. (C) 2010 Elsevier B.V. All rights reserved.